Британские интеллектуалы эпохи Просвещения: от маркиза Галифакса до Эдмунда Бёрка / Т. Л. Лабутина, М. А. Ковалев - Лабутина Татьяна Леонидовна (Pax Britannica, 2020)
Экземпляры: СЭ (20220228) / Инвентарный номер: 1117670 / Цена: / Сис.шифр: 63.3(4) / Авт.знак: Л 12 / ГРНТИ: 03 / ББК: 63.3(4Вел)5